State of Stresses and Fatigue Assessment for a Steel Truss Bridge - Igareta Moreno, Marta Cristina (2013)
The following master thesis State of stress and fatigue assessment for a steel truss bridge seeks with the help of the research group “Assessment, repair and strengthening” from Luleå University of Technology the possibility of assessing a unique project where two identical railway steel truss bridges, bridge over Åby river and bridge over Rautasjokk.Before the Åby river bridge was replaced last September 2012, was subjected to loading up and monitored and the findings will be compared to the bridge still in use (Rautasjokk). Not only the loading has been into consideration for the assessment of the bridge, but also different aspects, such as corrosion, bridge temperature and type of weldings, both riveting and welding, has been taken into consideration in the literature review of this study.According to the case study and the method used to analyse this study was based on the strain gauges located along one half of the Åby river bridge during the first twelve days of September 2012 before the bridge was replaced. With the data obtained with the previously mentioned gauges has been able to assess how every train passing deforms, and thus, affects the structure of the bridge with the help of the software Matlab.Also, knowing the strains and stresses that were obtained could be analysed how the beams were deformed, focusing on the most harmful train passage, giving us a reliable and precise data to compare with the Rautasjokk bridge and get to the conclusion that still the life span of the Rautasjokk Bridge is good enough to continue carrying such loads. Validerat; 20130712 (global_studentproject_submitter)